Short communication: The diversity of ureolytic bacteria isolated from limestone in East Java, Indonesia based on amino acid sequences encoded by ureC - ENNY ZULAIKA; M. A. PRIO UTOMO; N. HIDAYATUL ALAMI; N. DWIANITA KUSWYTASARI; MAYA SHOVITRI; RIDHO BAYUAJI; ENDRY N. PRASETYO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Zulaika E, Utomo MAP, Alami NH, Kuswytasari ND, Shovitri M, Bayuaji R, Prasetyo EN. 2019. Short communication: The diversity of ureolytic bacteria isolated from limestone in East Java, Indonesia based on amino acid sequences encoded by ureC. Biodiversitas 20: 2316-2320. Ureolytic bacteria isolated from limestone are capable to produce urease enzyme which can breaks down urea into carbonate (CO32), has been utilized for various building material bioremediation and restoration. In this present study, we figured out the diversity and genetic relationship of ? sub-unit ureC gene among six ureolytic bacteria (JA1, JB2, JB3, JA4, AK4, and SU1) which were isolated from limestone area in East Java province. PCR was conducted to detect the gene which encoded active site of urease, ureC. Followed by sequences translation using BLAST-X (Basic Local Alignment Search Tool) based on the name and function of formed proteins and then aligned to the conserved domain database. Furthermore, the functions and characters of formed proteins were described. Based on PCR results, all isolates showed 340 bp DNA band which indicate the presence of ureC gene. The results of BLAST-X, JB2 isolates showed 100% similarity with the ? sub-unit ureC gene from Lysinibacillus sphaericus B1-CDA (WP_054549252.1). Whereas, JA1 isolates showed 88% similarity (lowest) with the ? sub-unit ureC gene from Bacillus cihuensis FJAT-14515 (WP_028391929.1). The present study reveals that ureC phylogeny can be used in order to investigate ureolytic bacteria species which isolated from calcareous area in East Java province.